التعريض في شعر المتنبي: (دراسة تحليلية تطبيقية) - د. محمد الحسن مختار بلال; د. عبد الباقي يوسف البرير (White Nile Journal for Studies and Research, 2014)
Among the famous and public that a rivalry has intensified around Al-Mutanabi. controversy erupted for him and battles took place in the fields of his poetry. so the studies dealing with Al-Mutanabi poetry will not finish. but we see them increase a day after day. each one take them from a specific point of view. The linguist in terms of language, the rhetoric in terms of artistic images and the critic to broadcast his ideas. visions and so on... Periphrasis as an artistic value has won a good deal of interest of the ancients in their various specializations in Arabic and Koran sciences. The critical studies on Al-Mutanabi poetry have won a great fortune since the fourth century (AH) till today, but with all these studies on his literature. criticism, originality and imitation. Al-Mutanabi poetry still expands to other studies. The dimensions of the study are as follows - Al-Mutanabi. his life and his poetry characteristics. The concept of Periphrasis among linguists and rhetorics. Periphrasis in the poetry of Al-Mutanabbi.